The psychological problems resulting from the emerging corona virus (COVID-19) pandemic among female secondary school students in Madinah - Al-Ahmadi, Maha Jabir Musa; Al-Hadidi, Saud AbdulAziz (Journal of Educational and Psychological Sciences, 2022)
The research aimed to identify the nature and the most important psychological problems that high school students suffer from in private schools resulting from the emerging corona virus pandemic, the researcher used the descriptive-analytical method due to its relevance to the nature of the study, and a total of (2737) students were identified. The sample was chosen by an intentional random method for the academic year (2020/2021), and the number is (300) students, using an investigation form after presenting it to (13) arbitrators, and the most important results were that sleep disorders and eating disorders occupy an advanced position in the list of the most psychological problems experienced by adolescents and young adults, and there are statistically significant differences in the responses of the basic sample related to psychological problems that suffer from Including secondary school students in private schools in Madinah, which are the consequences of the new Corona virus pandemic, according to the variables of age and social level (high and low), where psychological problems increase with age, and social level (high) for the different dimensions, and for the scale of psychological problems as a whole, and that these differences real and in favor of (the high level), and the researcher recommended that the media should educate parents about the need to provide psychological support, especially in The age period under study, and holding scientific conferences to discuss the findings of scientific studies of the psychological impact of the emerging corona virus pandemic and to activate its recommendations.